HUBUNGAN PERSEPSI SISWA TERHADAP ETIKA GURU DAN PEMBENTUKAN KARAKTER PESERTA DIDIK DI SMAN 1 SUNGAI PENUH - Delima Afianti; Rahmi Putri (CV. ADIBA AISHA AMIRA, 2025)
This research seeks to examine the relationship between students’ views on the integrity of educators and the development of their personal virtues at MTsN 2 located in Sungai Banyak City. By administering a survey with like-dislike questions to 25 random students, we gathered numerical information.” The evaluation results show an important correlation between students’ views of educator integrity, particularly in honesty, equality, self-control, and compassion, and the development of these traits. Student traits such as accountability, teamwork, and independence. Pearson analysis shows a relationship index (r = 0.65) with statistical significance (p < 0.01), which indicates that the teacher’s disposition is very influential remaining data (p = 0.08) works, which supports the accuracy of our analysis. Rewrite the above phrase more concisely, using only synonyms while keeping the original meaning intact with ‘ ‘ important function of pedagogical integrity in fostering students’ moral development, supporting educators